Whole Body Imaging with Multi Detector Computed Tomography in Multitrauma Patients: A Retrospective Analysis - Surabhi Sharma; Sunita Dashottar (International Journal of Anatomy Radiology and Surgery, 2020)
Introduction: Trauma is the numero uno cause of death under 45 years of age and imaging evaluation is imperative, because clinical examinations alone can be unreliable in multitrauma patients. Aim: To evaluate the various trauma findings in blunt multitrauma patients who underwent whole body imaging with Multi Detector Computed Tomography (MDCT). Materials and Methods: A retrospective study was conducted in a tertiary care centre in which 75 cases of multitrauma were subjected to whole body imaging on MDCT from July 2017 to December 2018 after initial clinical examination by the trauma team. The trauma protocol followed in our centre was a twostep whole-body acquisition from vertex to pubic symphysis. In the first step, Non-Enhanced CT (NECT) acquisition of head and cervical spine was done. In the second step, acquisition of chest, abdomen and pelvis was done after a bolus intravenous contrast. The evaluation of data was done with the scanned body divided into six regions: head and face thoracic, abdomen, retroperitoneum, genito-urinary, spine and pelvic regions. Results: Mean age of our study population was 35.6±15.01 years. The leading trauma was due to road traffic accident in 67 cases (89.3%). Sixty four out of 75 (85.3%) had atleast one finding of trauma while 11(14.7%) had no findings in relation to trauma. Thirty six patients (48%) had findings in two regions, 11(14.7%) had findings in three regions and 4 (5.3%) had findings in four regions. Conclusion: In our study, 85.3% had findings of trauma involving one or more regions and only 14.7% had no findings of trauma, thus emphasising the aptness of whole body imaging with MDCT in multitrauma patients.